Tightening tax policy and changes to tax efficiency on the example of companies listed on the Warsaw Stock Exchange - Kowalski, Michał; Nesterak, Janusz (Managerial Economics, 2023)
The article presents an analysis of changes in the tax efficiency of companies listed on the Warsaw Stock Exchange. After 2017, some changes to the tax law aimed at tightening the regulations on an unprecedented scale were introduced. The research conducted showed that since 2018 there has been a decrease in tax efficiency measured with effective tax rate (ETR) and current effective tax rate (CETR). On average, in 2018–2019, the efficiency measured with CETR dropped by 17.7%, the median by 14.8% compared to the previous years. In 2018 and 2019, the value of the CETR was the highest in the entire analyzed period, i.e. from 2012 to 2019. At the same time, the propensity of companies to create deferred tax assets is declining, and the effective tax rate is also growing. The changes mainly concern companies with average tax efficiency, large entities forming capital groups, and companies implementing capital investments. The article presents a discussion on the observed trends and formulates directions for further research.